Baseline Performance of High School Rugby Players on the Sport Concussion Assessment Tool 5 - Black, Amanda M. (J Athl Train, 2020)
CONTEXT: Version 5 of the Sport Concussion Assessment Tool (SCAT5) was released in 2017 with an additional 10-word list option in the memory section and additional instructions for completing the symptom scale. OBJECTIVE: To provide reference scores for high school rugby union players on the SCAT5, including immediate memory using the 10-word list, and examine how age, sex, and concussion history affected performance. DESIGN: Cross-sectional study. SETTING: Calgary, Alberta high schools. PATIENTS OR OTHER PARTICIPANTS: High school rugby union players (ages 15–18 years) participating in a 2018 season cohort study (n = 380, males = 210, females = 170). MAIN OUTCOME MEASURE(S): Sport Concussion Assessment Tool 5 scores, including total number of symptoms (of 20), symptom severity (of 132), 10-word immediate memory (of 30), delayed memory (of 10), modified Standardized Assessment of Concussion (of 50), and balance examination (of 30). RESULTS: The median number of symptoms reported at baseline ranged from 5 to 8 across sex and age stratifications. Median symptom severity was lowest in males with no concussion history (7; range, 0–28) and highest in females with a concussion history (13, range = 0–45). Median total scores on immediate memory were 2–3 (range = 0–4) for males and 21 (range = 9–29) for females. Median total scores were 3 (range = 0–4) on digits backward and 7 (range = 0–20) on delayed memory (all groups). Based on simultaneous quantile (q) regression at 0.50 and 0.75, adjusted for age and concussion history, being female was associated with a higher total symptoms score (q0.75 β(female) = 2.85; 99% confidence interval [CI] = 0.33, 5.37), higher total symptom severity score (q0.75 β(female) = 8.00; 99% CI = 2.83, 13.17), and lower number of errors on the balance examination (q0.75 β(female) = −3.00; 99% CI = −4.85, −1.15). Age and concussion history were not associated with any summary measures. CONCLUSIONS: The 10-word list option in the memory section reduced the likelihood of a ceiling effect. A player's sex may be an important consideration when interpreting the SCAT5 after concussion.